Academic library services for first-generation students - Arch, Xan; Gilman, Isaac (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2020)
"Presenting strategies for improving academic library services for first-generation students, this timely book focuses on programs and services that will increase student academic engagement and success"--